Mineralisation of sulfolane by UV/O3/H2O2 in a tubular reactor. Issue 2 (3rd October 2016) - Mehrabani-Zeinabad, Mitra; Yu, Linlong; Achari, Gopal; Langford, Cooper H.
Abstract : Degradation of sulfolane in contaminated groundwater was studied in a flow-through photoreactor with recirculation, using various oxidative methods, including ozone (O3 )/hydrogen peroxide (H2 O2 ), ultraviolet (UV)/ozone, UV/hydrogen peroxide and UV/ozone/hydrogen peroxide. Total organic carbon as an indicator of the extent of mineralisation and sulfate as a byproduct produced during degradation were measured. The effects of several operating conditions, including flow rate, initial concentration of sulfolane and ratio of different oxidants, were investigated. It was noted that although the loss of sulfolane was similar for the UV/ozone/hydrogen peroxide and the UV/hydrogen peroxide process, the overall mineralisation rates were significantly different, indicating that the combination of oxidants offers a significantly more efficient system. The results show that in water containing 100 mg/l sulfolane, more than 99·5% can be mineralised to carbon dioxide (CO2 ), water (H2 O) and sulfate (SO4 2− ) by the UV/ozone/hydrogen peroxide process (the most efficient process) within 4 h (13·2 kJ energy from UV irradiation transferred). The UV/ozone/hydrogen peroxide process mineralised sulfolane in contaminated groundwater, but with a longer reaction time.